Sediment elemental and stable isotopic composition of sediment cores from the northern Barents Sea - Thaise Ricardo de Freitas; Silvia Hess; Paul E Renaud; Peter G Appleby; Elisabeth Alve (PANGAEA, 2025)
Sediment cores (40 cm long, 10 cm diameter) were retrieved at nine stations (NPAL04 to NPAL19) with a four-tube multi-corer. Additionally, one short sediment core (6 cm length x 5 cm diameter) was subsampled from a giant box corer deployment at station P1. All sediment cores were immediately sliced into 1 cm layers, and subsamples were directly frozen on board ( 20 °C). Sediment elemental (C, N) and stable isotopic composition (δ13C, δ15N) of these radiometrically dated cores were investigated, along with grain size, at all ten sampled stations. Carbon and nitrogen analysis was undertaken with an Elemental Analyser Isotope Ratio Mass Spectrometry (EA-IRMS; Iso-Analytical Ltd., UK), whereas grain size distribution of non-acidified samples was assessed with a Beckman Coulter LS 13 320 Particle Size Analyser. The isotope ratios analytical error was determined by calculating the standard deviation of repeated measurements of reference standards (≤0.07 extperthousand for δ13C and ≤0.15 extperthousand for δ15N).
In: Ricardo de Freitas, T et al. (2025): Sedimentary and geochemical properties of sediment cores from the northern Barents Sea [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.986961